The recurrent TCF4 missense variant p.(Arg389Cys) causes a neurodevelopmental disorder overlapping with but not typical for Pitt‐Hopkins syndrome. Issue 6 (16th August 2022) - Popp, Bernt; Bienvenu, Thierry; Giurgea, Irina; Metreau, Julia; Kraus, Cornelia; Reis, André; Fischer, Jan; Bralo, María Palomares; Tenorio‐Castaño, Jair; Lapunzina, Pablo; Almoguera, Berta; Lopez‐Grondona, Fermina; et al.
Abstract: TCF4 haploinsufficiency by deletions, truncating variants or loss‐of‐function missense variants within the DNA‐binding and protein interacting bHLH domain causes Pitt‐Hopkins syndrome (PTHS). This neurodevelopmental disorder (NDD) is characterized by severe intellectual disability (ID), epilepsy, hyperbreathing and a typical facial gestalt. Only few aberrations of the N‐terminus of TCF4 were associated with milder or atypical phenotypes. By personal communication and searching databases we assembled six cases with the novel, recurrent, de novo missense variant c.1165C > T, p.(Arg389Cys) in TCF4 . This variant was identified by diagnostic exome or panel sequencing and is located upstream of the bHLH domain. All six individuals presented with moderate to severe ID with language impairment. Microcephaly occurred in two individuals, epilepsy only in one, and no breathing anomalies or myopia were reported. Facial gestalt showed some aspects of PTHS but was rather non‐specific in most individuals. Interestingly, the variant is located within the AD2 activation domain next to a highly conserved coactivator‐recruitment motif and might alter interaction with coactivator proteins independently from the bHLH domain. Our findings of a recurrent missense variant outside the bHLH domain in six individuals with an ID phenotype overlapping with but not typical for PTHS delineate a novel genotype–phenotype correlation for TCF4 ‐related NDDs. Abstract :